Psychometric Characteristics of the Central Mathematics Test for the First Intermediate Grade in Al-Madinah Almunawarah’s schools - Al-Harbi, Ibrahim Bin Abdul-Rahman (Journal of Educational and Psychological Sciences, 2020)
The present study aimed at identifying the psychometric characteristics of the central mathematics test For the first grade, which was applied during the second semester of 1438/1439 AH, The study covered objective questions of (40) multiple-choice clauses and (10) true or false questions, in order to achieve the objectives of the study, (372) students were selected among (12484) students, After being introduced and analyzed through the (SPSS) program, Version 25, the study found a number of results as the stability coefficient of the Alpha Cronbach (0.89) which means that it is very high, There was found that the validity of the test was very high and that was supported by strong indicators. In view of the characteristics of the questions, the difficulty coefficient of the statements of the questions ranged between (0.30- 0.82), Their ability to discrimination factor is very acceptable, with most of them ranging from (0.20 – 0.58), The distractors were very effective in attracting student attention, which emphasizes the quality of the psychometric properties of the statements of the questions. Based on the results of this study, it is shown that the quality of the psychometric characteristics of this test is very high. The researcher recommended expanding the application of the test optimization project (central tests) to include all the subjects in the intermediate stage, taking into consideration the availability of indicators of the validity of the content, And training those in charge of this project and teachers in general on the skill of formulating highly effective vocabulary in multiple-choice questions, and the researcher recommends that teachers use the materials more to build a question bank, which can be used later in preparing pictures equivalent to the tests, Which was not addressed in this study and training those in charge of this project and teachers in general on the skill of formulating highly effective vocabulary in multiple-choice questions, and the researcher recommends that teachers use the materials more to build a question bank, which can be used later in preparing pictures equivalent to the tests.